Tuft-cell-derived IL-25 regulates intestinal ILC2 in response to Brucella infection - Shang, Kaiyu; Chen, Na; Tian, Tingting; Shi, Huidong; Shi, Juan; Qi, Xinxin; Zhu, Yuejie; Zhang, Fengbo (Frontiers in Immunology, 2026)
IntroductionBrucella is a zoonotic pathogen capable of invading the host through the intestinal mucosa. However, the immune mechanisms underlying intestinal infection remain poorly understood. Tuft cells are specialized chemosensory epithelial cells in the intestine that can detect pathogen invasion and secrete IL-25, subsequently activating type 2 innate lymphoid cells (ILC2s) and playing a critical role in anti-parasitic immune responses. Nevertheless, whether the tuft cell-ILC2 circuit participates in immune responses against bacterial infections remains unclear. This study aimed to investigate the dynamic changes of tuft cells and ILC2s following Brucella infection, with a particular focus on elucidating the regulatory role of IL-25 in this process.MethodsThirty-six mice were divided into six groups: normal control (NC), isotype control (IC), infection groups at different time points (3, 7, and 14 days post-infection, designated as Inf-3d, Inf-7d, and Inf-14d, respectively), and an IL-25 blockade group (IL-25 Blk-7d, in which mice received anti-IL-25 neutralizing antibody treatment prior to Brucella infection and were analyzed at 7 days post-infection). In this study, immunofluorescence assay, flow cytometry, and Western blot were employed to detect the dynamic changes of tuft cells and ILC2s in intestinal tissues, as well as to determine the expression levels of pathway-related proteins.ResultsThe results showed that the numbers of tuft cells and ILC2s in the mouse intestine increased following Brucella infection, peaking at 7 days post-infection. Pretreatment with IL-25 neutralizing antibody significantly suppressed the proliferation of these two cell populations. Western blot analysis further confirmed that the expression levels of tuft cell-associated proteins (PO2F3, DCLK1, and IL-25) and ILC2-associated proteins (GATA3 and IL-13) were upregulated in infected intestinal tissues, whereas IL-25 blockade treatment inhibited the expression of these proteins. Correlation analysis revealed a remarkably strong positive correlation between the proportions of tuft cells and ILC2s, and this correlation was completely abolished following IL-25 neutralization.DiscussionThese findings confirm that the activation of the tuft cell-ILC2 circuit is dependent on the regulatory role of IL-25. These findings extend the antimicrobial role of the tuft cell-ILC2 circuit beyond parasitic immunity and identify IL-25 as an essential regulatory mediator in antibacterial defense at the intestinal mucosa.